2015
DOI: 10.4269/ajtmh.15-0237
|View full text |Cite
|
Sign up to set email alerts
|

Enalapril in Combination with Benznidazole Reduces Cardiac Inflammation and Creatine Kinases in Mice Chronically Infected with Trypanosoma cruzi

Abstract: Abstract. The protozoan Trypanosoma cruzi triggers an inflammatory process in mammalian

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 48 publications
(55 reference statements)
1
23
0
Order By: Relevance
“…Most studies indicated that RAS-modulating drugs were effective in reducing parasitaemia (Chumbinho et al ., 2012; Leite et al ., 2017) and mortality (de Paula Costa et al ., 2010; Chumbinho et al ., 2012; Penitente et al ., 2015). Conversely, parasitaemia was unchanged by enalapril (Penitente et al ., 2015), while high doses of captopril (75 mg L −1 ) increased the animals’ mortality with no impact on heart parasitism (Leon et al ., 2003).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies indicated that RAS-modulating drugs were effective in reducing parasitaemia (Chumbinho et al ., 2012; Leite et al ., 2017) and mortality (de Paula Costa et al ., 2010; Chumbinho et al ., 2012; Penitente et al ., 2015). Conversely, parasitaemia was unchanged by enalapril (Penitente et al ., 2015), while high doses of captopril (75 mg L −1 ) increased the animals’ mortality with no impact on heart parasitism (Leon et al ., 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies indicated that RAS-modulating drugs were effective in reducing parasitaemia (Chumbinho et al ., 2012; Leite et al ., 2017) and mortality (de Paula Costa et al ., 2010; Chumbinho et al ., 2012; Penitente et al ., 2015). Conversely, parasitaemia was unchanged by enalapril (Penitente et al ., 2015), while high doses of captopril (75 mg L −1 ) increased the animals’ mortality with no impact on heart parasitism (Leon et al ., 2003). In general, RAS-modulating drugs increased IL-10 plasma levels (Penitente et al ., 2015; Leite et al ., 2017) and reduced TNF- α , IFN- γ , CCL2 circulating levels and myocarditis severity (de Paula Costa et al ., 2010; Penitente et al ., 2015; Leite et al ., 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These mice were maintained under the same conditions as the other animals (acclimation period: 4 weeks). New animals were required since the peak of parasitemia occurred 27 days after infection; in the original group, this peak occurred before the enrichment treatment, preventing assessment of parasitemia 35 .…”
Section: Tablementioning
confidence: 99%
“…On the other hand, chronic cardiac inflammation induced by T. cruzi is a harmful and silent event that occurs due to the failure in resolving the acute inflammation and/or due to the persistence of the parasitic stimulus. The involvement and importance of CK and CKR to the generation of the chronic cardiomyopathy induced by T. cruzi were previously highlighted by our group, in humans and in experimental animals (rodent and dog) [ 12 , 14 17 ]. Even at this chronic stage, IFN- γ and TNF persist as essential cytokines, maintaining the migration of T cells to consolidate the cardiomyopathy by increasing the expression of CCL5 (RANTES), CCL2 (MCP-1), CXCL10 (IP-10), and CXCL9 (MIG) as well as enhancing intercellular adhesion and vascular cell adhesion molecules [ 7 , 12 ].…”
Section: Introductionmentioning
confidence: 96%